2021
DOI: 10.21203/rs.3.rs-533063/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Emergence of a noncollinear magnetic state in twisted bilayer CrI3

Abstract: The emergence of two-dimensional (2D) magnetic crystals and moiré engineering of van der Waals materials has opened the door for devising new magnetic ground states via competing interactions in moiré superlattices. Although a suite of interesting phenomena, including multi-flavor magnetic states, noncollinear magnetic states, moiré magnon bands and magnon networks, has been predicted in twisted bilayer magnetic crystals, nontrivial magnetic ground states have yet to be realized. Here, by utilizing the stackin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 41 publications
4
11
0
Order By: Relevance
“…These nontrivial phases arise from the competition between the interlayer AFM coupling in the monoclinic stacking regions of the moiré superlattice and the energy cost to form AFM–FM domain walls. Our results agree with recent magnetic circular dichroism (MCD) experiments in CrI 3 and provide insights for the wealth of noncollinear magnetic phases that can potentially be obtained in twisted bilayer chromium trihalides.…”
supporting
confidence: 88%
See 1 more Smart Citation
“…These nontrivial phases arise from the competition between the interlayer AFM coupling in the monoclinic stacking regions of the moiré superlattice and the energy cost to form AFM–FM domain walls. Our results agree with recent magnetic circular dichroism (MCD) experiments in CrI 3 and provide insights for the wealth of noncollinear magnetic phases that can potentially be obtained in twisted bilayer chromium trihalides.…”
supporting
confidence: 88%
“…These layered materials consist of ferromagnetic planes of Cr 3+ : d 3 cations arranged in a honeycomb lattice with edge-sharing octahedral coordination. Bulk CrX 3 materials exist in two structural phases with different stacking sequences along the c axis: a low-temperature rhombohedral structure and a high-temperature monoclinic structure. , Recently, it has been shown that the stacking pattern in CrX 3 bilayers can give rise to a sign change in the interlayer magnetic coupling. This stacking-dependent interlayer magnetic exchange has been experimentally demonstrated in both CrI 3 and CrBr 3 , with the monoclinic stacking supporting an antiferromagnetic (AFM) interlayer coupling, while the rhombohedral stacking supports a ferromagnetic (FM) coupling instead. This result has important implications for the moiré physics: a small twisting in bilayers creates a long-period moiré pattern, in which the stacking order in each local region is similar to the corresponding lattice-matched stacking configuration. As such, the competing stacking-dependent interlayer interactions can give rise to novel magnetic states upon twisting, as recently demonstrated for CrI 3 …”
mentioning
confidence: 84%
“…This result is compatible with a recent experimental work on this system. [ 49 ] The origin of these transitions are due to the changes in the distribution of the n.n. and n.n.n.…”
Section: Discussionmentioning
confidence: 99%
“…Emergent gauge field at large exchange coupling.-In the following, we explore the consequences of a large exchange coupling on the electronic bandstructure. This is motivated by both the giant exchange splitting found in the previous section and theoretical and experimental results suggesting that twisted bilayers of vdW magnets may host noncoplanar or skyrmionic phases [27][28][29][30][31].…”
mentioning
confidence: 90%
“…In this work, we propose a new platform for a topological flat band in 2D magnet/ TMD semiconductor heterostructures, in which the magnetic exchange coupling introduces an emergent Zeeman field acting on a low density of carriers in the semiconductor. Our study is motivated by the recent theoretical [27][28][29][30] and exper-imental works [31] suggesting the existence of skyrmion phases and periodic chiral spin textures arising from a spatially varying interlayer coupling in magnetic moirés such as twisted bilayers of CrI 3 or CrBr 3 . Our two main results are as follows.…”
mentioning
confidence: 99%